Body dissatisfaction and smartphone addiction among Chinese adolescents: A moderated mediation model. (January 2020) - Liu, Qinxue; Sun, Jianing; Li, Qiuling; Zhou, Zongkui
Highlights: Body dissatisfaction (BD) positively predicted smartphone addiction (SA). Positive self-presentation (PSP) mediated the link between BD and SA. The mediating role of PSP was moderated by friendship quality (FQ). Abstract: Based on compensatory satisfaction theory, the present study examined the relation between body dissatisfaction and adolescent smartphone addiction, as well as the roles of positive self-presentation on social networking sites and friendship quality. A sample of 1036 Chinese adolescents from 11 to 15 years of age (mean age = 12.41 years, SD = 0.65) responded to anonymous questionnaires regarding body dissatisfaction, friendship quality, positive self-presentation on social networking sites and smartphone addiction. The results indicated that body dissatisfaction could positively predict adolescent smartphone addiction. In addition, positive self-presentation on social networking sites mediated the relation between body dissatisfaction and smartphone addiction. Moreover, the first part of the mediating effect (i.e., the link from body dissatisfaction to positive self-presentation on social networking sites) was moderated by friendship quality, with the effect being significant only for adolescents with low levels of friendship quality. The present study can advance our understanding about smartphone addiction and how human interact with technology. Limitations and implication about the present study are also discussed.